Pengaruh Metode Pembelajaran Kolaborasi terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran PAI - Raito, Raito; Nurzanah, Putri Arfah (STAI Al-Musaddadiyah Garut, 2025)
The era of globalization that we are currently experiencing, accompanied by rapid social changes, also affects students' understanding of learning materials, including in religious education. Although there is an increase in students' cognitive learning outcomes in Islamic Religious Education (PAI) subjects, the results are not yet satisfactory. In addition, the low level of their activeness and discipline during the learning process is also a significant challenge. Therefore, it is important to find an effective method to improve their understanding and learning achievement. The collaborative learning method was adopted because of its ability to increase student involvement, strengthen interactions between them, and encourage discussion and deeper understanding of PAI materials. This study aims to describe the effect of the collaborative learning method on student learning outcomes in PAI subjects phase D at SMP IT Husnul Khotimah Wanaraja Garut. In this study, the approach used is descriptive quantitative, with data collection through observation, documentation studies, and questionnaires distributed to 60 students as samples. Data processing is carried out through statistical analysis. The results of the analysis show that the collaborative learning method has a significant influence. This study revealed that the contribution of the studied factors to the cognitive learning outcomes of students reached 34.9%. On the other hand, the contribution to affective learning outcomes was 20.6%, and to psychomotor learning outcomes reached 15.6%. However, there were also other factors that contributed to cognitive learning outcomes up to 65.1%, affective learning outcomes by 79.4%, and psychomotor learning outcomes by 84.4%. It should be noted that although these factors have a large influence, they were not analyzed further in this study. Keywords: collaborative learning methods, student learning outcomes, islamic religious education